Dissolved Organic Phosphorus Utilization by Phytoplankton Reveals Preferential Degradation of Polyphosphates Over Phosphomonoesters - Diaz, Julia M.; Holland, Alisia; Sanders, James G.; Bulski, Karrie; Mollett, Douglas; Chou, Chau-Wen; Phillips, Dennis; Tang, Yuanzhi; Duhamel, Solange (Frontiers in Marine Science, 2018)
The nutritionally available pool of dissolved organic phosphorus (DOP) supports marine primary productivity in a range of ocean ecosystems but remains poorly resolved. Here, the relative lability of model phosphorous (P) compounds representing the major P(V) bond classes of marine DOP – phosphomonoesters (P-O-C) and phosphoanhydrides (P-O-P) – was assessed in diatom cultures of the genus Thalassiosira, as well as coastal field sites of the western North Atlantic. In diatom samples, maximum enzymatic hydrolysis rates revealed that the P-anhydride bonds of inorganic tripolyphosphate (3poly-P), followed by the P-anhydride bonds of adenosine 5’-triphosphate (ATP), were preferentially degraded relative to the P-monoesters adenosine 5’-monophosphate (AMP) and 4-methylumbelliferone phosphate (MUF-P). Consistent with these rate measurements, targeted proteomics analysis demonstrated that the underlying phosphatase diversity present in diatom samples was dominated by P-anhydride degrading enzymes (inorganic pyrophosphatases and nucleoside triphosphatases). Furthermore, biomass-normalized rates of ATP degradation were always suppressed under P-replete conditions in diatom cultures, but the effect of overall P availability on 3poly-P degradation was inconsistent among diatom strains, suggesting that inorganic polyphosphate (poly-P) degradation may persist irrespective of prevailing P levels in the marine environment. Indeed, the majority of field sites examined in the P-replete coastal western North Atlantic exhibited significantly higher maximum rates of inorganic poly-P hydrolysis relative to P-monoester hydrolysis, which was largely driven by phytoplankton dynamics. Based on these results, the possibility that P-anhydride utilization may contribute comparably or even more substantially than P-esters to community-level P demand, phytoplankton growth, and primary productivity should be considered.